Suitability of searching and representing multimedia learning resources in a three-dimensional virtual gaming environment - Rahman, Abu Saleh Md. Mahfujur (University of Ottawa (Canada), 2007)
Search engines usually publish search results in web pages that are filled with a certain number of matched records that can be navigated further through successive back and forth operations. While this approach proves to be useful, it fails to show the context and relationship among displayed results. We argue that new and intuitive user interfaces, such as a 3D virtual environment, may provide an alternative to the traditional presentation techniques, especially in a learning environment where learners are looking for multimedia learning resources that match their interests. We propose a 3D car gaming environment as a search metaphor and analyze the suitability of such an approach in terms of user perception, interaction, visual quality, graphics rendering performance and other parameters. Our experiment suggests that the proposed approach not only shows an intuitive way of information visualization but also integrates education and entertainment to serve the vision of Edutainment.
Keywords: Computer Science.